Ultra–low-dose radiotherapy for definitive management of ocular adnexal B-cell lymphoma - Pinnix, Chelsea C. (Head Neck, 2017)
BACKGROUND. The purpose of this study was to report the response to and toxicity of ultra–low-dose radiotherapy (RT) for B-cell ocular adnexal lymphoma (OAL). METHODS. We conducted a retrospective review of patients with indolent B-cell and mantle cell OAL treated with 4 Gy to the orbit(s) in two 2-Gy fractions. Disease response was assessed clinically and/or radiographically at 2 to 4-month intervals after RT. Data collected included rates of overall response, complete response (CR), partial response (PR), and treatment-related toxic effects. RESULTS. Twenty-two patients (median age, 65 years) had the following histologic subtypes: mucosa-associated lymphoid tissue (MALT; 14 patients; 64%); follicular lymphoma (5 patients; 23%); mantle cell lymphoma (MCL; 2 patients; 9%); and unclassifiable (1 patient, 4%). The overall response rate was 100%; 19 patients (86%) had a CR and 3 patients (14%) had a PR. The only acute toxic effect was grade 1 dry eye syndrome in 1 patient. CONCLUSION. Ultra–low-dose RT in patients with OAL is associated with high response rates and minimal toxic effects, and is much shorter in duration and cost.